Biosynthesis of ZnO Nanoparticles Using Pumpkin Peel Extract (Cucurbita moschata) and its Applications as Semiconductor in Dye Sensitized Solar Cell (DSSC) - Nanda Saridewi; Dzikri Anfasa Firdaus; Isalmi Aziz; Biaunik Niski Kumila; Dasumiati Dasumiati (Jurnal Kimia Valensi, 2021)
ZnO nanoparticles are semiconductor materials that can be used in Dye Sensitized Solar Cells (DSSC). ZnO nanoparticles can be synthesized using pumpkin peel extract (Cucurbita moschata) which functions as a reducing agent, stabilizer, and capping agent. Zn(CH3COO)2.2H2O precursor was used with a concentration of 0.15 M at various pH 7, 8, and 9 reacted with pumpkin peel extract. The functional groups of pumpkin peel extract were characterized using Fourier Transform Infrared Spectroscopy (FTIR), the samples were analyzed by TEM and XRD. The resulting ZnO nanoparticles were used as semiconductors in Dye Sensitized Solar Cell (DSSC) using dyes from mangosteen peel.The FTIR results showed the presence of functional groups O-H hydroxy, CH2, secondary amides (R-CO-NR2, C-H and phosphate (PO43-). XRD results showed that ZnO produced wurzhite crystals with a hexagonal system and the smallest crystal size was 18.99 nm. TEM results showed that ZnO synthesized at a concentration of 0.15 M and pH 8 had a spherical particle shape with a size of 24.90 nm, while the DSSC test results had an efficiency of 9.06 x 10-4%.